KECERNAAN BAHAN KERING DAN BAHAN ORGANIK KAMBING KACANG JANTAN YANG DIBERI NAUNGAN DAN TANPA NAUNGAN DI LAHAN KERING KEPULAUAN - Molbeka Marthina Manikari; Bambang Hadisutanto; Jacobus S. Oematan; Bachtaruddin Badewi (Partner, 2020)
Heat stress due to high ambient temperature results in uncomfortable livestock and unfavorable physiological changes. This condition causes livestock to not be able to maintain the balance of thermal energy, water, hormonal, mineral and feed consumption and consumption of dry matter is reduced so that digestibility of dry matter and organic matter also decreases. The purpose of this study was to determine the digestibility of dry matter and organic material of male goats in the shed without shade and with shade. The materials used in this study were 1 year old male goat, animal feed in the form of gamal leaves (Gliricidia sepium) and elephant grass, anthelmintic levamison, concentrated feed consisting of yellow corn flour, rice bran, soybean meal. and pollard.Variables observed included dry matter digestibility and organic matter digestibility. The research design used was placing 14 goat nuts allocated in 2 places, 7 of which were placed in a shed with 7 shelters and placed in a shed without a shade. Then the research data were analyzed using the t test (t-student).The results of this study are the digestibility of dry matter and organic material of male goat without shade and with no significant shade (P> 0.05) Keywords: Goat Male, Dry material digestibility, Organic material digestibility